2015
DOI: 10.1089/tmj.2015.0029
|View full text |Cite
|
Sign up to set email alerts
|

The Empirical Evidence for the Telemedicine Intervention in Diabetes Management

Abstract: Objective: The research presented here assesses the scientific evidence for the telemedicine intervention in the management of diabetes (telediabetes), gestational diabetes, and diabetic retinopathy. The impetus derives from the confluence of high prevalence of these diseases, increasing incidence, and rising costs, while telemedicine promises to ameliorate, if not prevent, type 2 diabetes and its complications. Materials and Methods: A purposeful review of the literature identified relevant publications from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 119 publications
(182 reference statements)
0
52
0
2
Order By: Relevance
“…There is limited evidence that fewer outpatient visits may be needed for women with GDM using telemedicine systems [38]. We did not identify any formal health economic evaluations of telemedicine systems for gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited evidence that fewer outpatient visits may be needed for women with GDM using telemedicine systems [38]. We did not identify any formal health economic evaluations of telemedicine systems for gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…With 1 in 3 people on the planet predicted to own a mobile phone by the end of 2016 [9], there is great enthusiasm among both patients and health care professionals to harness digital technologies to improve human health. In line with this, the number and sophistication of apps developed specifically for women with diabetes in pregnancy has increased [10,11]. Digital technologies in this patient group have most commonly been used to record and transmit blood glucose readings to the clinical care team between outpatient visits.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine systems, widely applied to diabetes care, have shown that they are able to improve clinical outcomes and selfcare by registering electronically diabetes monitoring data [9][10][11], and are especially useful in rural areas where, due to a lack of health care professionals, patients have to travel tens of kilometres to reach the specialized assistance [12]. In GDM, telemedicine has proven to reduce face-to-face visits as it allows remote patient monitoring so visits are only scheduled if a change in the therapy is required [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…23 Telemedicine for DR screening has the potential to grow rapidly as a result of these successes. [24][25][26] Despite the promise of telemedicine for DR, we do not understand patients' perceptions of telemedicine for eye disease management. Patient satisfaction with DR telemedicine varies widely from 35% to 99%.…”
Section: Introductionmentioning
confidence: 99%